Impact of plasma -treatment Water on the growth and germination Of Vicia Faba L - Mekhadmi Nour El houda; Amara Ghemam Djilani; Mlik Randa; Messaoudi Mohammed (Sousse, Tunisia, 2024)
أجريت هذه التجربة بكلية العلوم الطبيعية والحياتية جامعة الوادي سنة 2023 بهدف تحديد تأثير مياه الري المعالجة بالبلازما على نمو وإنبات نباتات أصناف. صممت التجربة باختيار 18 أصصاً لكل صنف، مقسمة إلى ست معاملات (بذور غير معاملة بالماء العادي، بذور معاملة بالماء العادي الجاف، بذور معاملة بالماء العادي الرطب، بذور غير معاملة بالماء المعالج، بذور معاملة بالماء الجاف العادي، ومعاملة البذور بالماء المعالج الرطب) بواقع ثلاث مكررات لكل معاملة. أظهرت النتائج المتحصل عليها أن المياه المعالجة بالبلازما لها تأثير واضح على الصفات المورفولوجية والفسيولوجية خلال مرحلتي الإنبات والنمو لصنفي فيتو هيستال وهابا فافا. وأدى إلى زيادة في القياسات الخضرية المختلفة والمعايير الكيميائية. وهذا يدل على أن المياه المعالجة بالبلازما لها فعالية نسبية في التأثير إيجابياً على نمو وإنبات نباتات Vicia faba L في صنفي Fito Histal وHaba Fava. Abstract: This experiment was conducted at the Faculty of Natural and Life Sciences, University of El Oued, in 2023, with the aim of determining the effect of plasma treated irrigation water on the growth and germination of Vicia faba L plants of the Fito Histal and Haba Fava varieties. The experiment was designed by selecting 18 pots for each variety, divided into six treatments (untreated seeds with regular water, treated seeds with dry regular water, treated seeds with wet regular water, untreated seeds with treated water, treated seeds with dry treated water, and treated seeds with wet treated water), with three replicates for each treatment. The results obtained showed that plasma-treated water had a clear effect on the morphological and physiological characteristics during the germination and growth stages of the Fito Histal and Haba Fava varieties. It led to an increase in various vegetative measurements and chemical criteria. This demonstrates that plasma-treated water has a relative effectiveness in positively affecting the growth and germination of Vicia faba L plants in both the Fito Histal and Haba Fava varieties.
Intervention
Keywords: فيسيا فابا إل; فيتو هيستال; هابا فافا; مياه معالجة بالبلازما; Vicia faba L; Fito Histal; Haba Fava; plasma-treated water.